"Xenotransplantation challenges us as a society": What well‐informed citizens think about xenotransplantation. (11th August 2020) - Kögel, Johannes; Marckmann, Georg
Abstract : A citizen's conference on xenotransplantation delivers a cautious 'Yes, but…' endorsement. It also shows how additional knowledge and debate shifted peoples' opinion on this technology.